3D Electronic Devices: Hexahedral LED Arrays with Row and Column Control Lines Formed by Selective Liquid‐Phase Plasticization and Nondisruptive Tucking‐Based Origami (Adv. Mater. Technol. 6/2020). Issue 6 (11th June 2020) - Kim, Gi‐Gwan; Kim, Yeongmin; Yoo, Seonggwang; Jang, Hun Soo; Ko, Heung Cho
Abstract : In article number 2000010, Heung Cho Ko and co‐workers develop 3‐dimensional electronic devices based on selective plasticization and tucking‐based origami. Confining a liquid plasticizer within a spacially designed microfluidic channel allows extreme folding to create a hexahedral light‐emitting diode with electrical row and column lines.